Toward a molecular understanding of adaptive immunity: a chronology, part I - Smith, Kendall A. (Frontiers in Immunology, 2012)
The adaptive immune system has been the core of immunology for the past century, as immunologists have been primarily focused on understanding the basis for adaptive immunity for the better part of this time. Immunological thought has undergone an evolution with regard to our understanding as the complexity of the cells and the molecules of the system became elucidated. The original immunologists performed their experiments with whole animals (or humans), and for the most part they were focused on observing what happens when a foreign substance is introduced into the body. However, since Burnet formulated his Clonal Selection Theory we have witnessed reductionist science focused first on cell populations, then individual cells and finally on molecules, in our quests to learn how the system works. This review is the first part of a chronology of our evolution toward a molecular understanding of adaptive immunity.